AB0457 OBSTETRICAL OUTCOME AND TREATMENTS DURING PREGNANCY IN SERONEGATIVE PRIMARY APS: DATA FROM EUROPEAN RETROSPECTIVE STUDY. (2nd June 2020) - Abisror, N.; Nguyen, Y.; Marozio, L.; Esteve-Valverde, E.; Udry, S.; Pleguezuelo, D. E.; Billoir, P.; Mayer-Pickel, K.; Urbanski, G.; Zigon, P.; De Moreuil, C.; Hoxha, A.; et al.
Abstract : Background: Objectives: To compare clinical characteristics, pregnancies, and treatments during pregnancies of seronegative and seropositive APS, and analyse factors associated with adverse obstetrical outcomes. Methods: Inclusion criteria were: (1) thrombotic arterial and/or venous; and /or obstetrical primary clinical APS (Sydney criteria); (2) absence of conventional antiphospholipid antibodies; (3) presence of at least one non-conventional APL among IgA ACL, IgA antiB2GPI, anti-vimentin G/M, anti-annexin V G/M, anti-PE G/M, anti-PS/PT G/M antibodies. The exclusion criteria were: (1) seropositive APS with conventional APS; (2) associated SLE or SLE like (SLE features and / or positive antinuclear autoantibodies); (3) other systemic connective tissue disease (Sjogren's syndrome, systemic sclerosis, myositis). Results: 187 women (mean 33±5 years) with seronegative APS were included from 12 centers in the world and compared to 285 patients with seropositive APS. Seronegative APS have mostly obstetrical phenotypes rather than venous thrombosis in comparison to seropositive APS. The maternal and fetal outcomes and the rates of live births were not significantly different in seronegative and seropositive APS, except for higher rates of intrauterine deaths (15% vs 5%; p=0.03) and lower live birth term (36±3 vs 38±3 weeks of gestation; p=0.04) in the seropositive APS group. The cumulative incidence of adverse obstetrical events was significantly improved in treated seronegative APS vs untreated ones (log rank<0.05), whereas there was no difference between patients who received aspirin or aspirin-LMWH combination Conclusion: Patients with clinical manifestations of APS without conventional APL should undergo testing for non-criteria APL. The diagnosis of seronegative APS could be important for a better care of these patients. Disclosure of Interests: None declared